ANALISIS YURIDIS PENERAPAN SANKSI PIDANA TERHADAP PELAKU KORUPSI DANA DESA DAN DAMPAKNYA TERHADAP KESEJAHTERAAN MASYARAKAT - Rahayu, Devi; Sulisetyaningsih, Dyah Nan; Rosyitawati, Unun Kholisa; Zulfikar, Pandri (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This study aims to comprehensively analyze the implementation of criminal sanctions against perpetrators of village fund corruption and its multidimensional impact on rural community welfare. The research employs a normative juridical method using statutory regulations, court decisions, and relevant legal literature as primary data sources. The findings indicate that village fund corruption constitutes an abuse of authority that fulfills the elements of criminal corruption as regulated under Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes. Corruption practices are carried out through various modus operandi, including budget embezzlement, project mark-ups, fictitious accountability reports, and misappropriation of funds for personal gain. Criminal sanctions are imposed through imprisonment, fines, and state financial loss restitution; however, sentencing disparities persist, rendering the deterrent effect suboptimal. Village fund corruption significantly impedes infrastructure development, diminishes the effectiveness of community empowerment programs, exacerbates social inequality, and erodes public trust in village government. Furthermore, village fund corruption is strongly correlated with the decline of the Human Development Index in rural areas, reflecting the state's failure to fulfill the basic rights of village residents. Therefore, combating village fund corruption requires firm and consistent law enforcement, strengthened community-based supervision systems, enhanced transparency in digital village financial management, and increased capacity-building of village officials in order to achieve clean, transparent, and accountable village governance oriented toward sustainable community welfare.